2014
DOI: 10.1002/acr.22270
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inflammatory Biomarkers and Bone Mineral Density in a Community‐Based Cohort of Men and Women

Abstract: OBJECTIVE Based upon evidence in animal and in-vitro studies, we tested the hypothesis that higher serum concentrations of the cytokines interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and the inflammatory marker C-reactive protein (CRP) would be inversely associated with BMD in a community-based cohort of men and women, with the strongest associations among post-menopausal women not using menopausal hormone therapy (MHT). METHODS We ascertained fasting serum concentrations of IL-6, TNF-α, and CRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 58 publications
3
37
2
Order By: Relevance
“…Our result that CRP plasma concentration was negatively correlated with relative bone mass and strength values is in contrast to a previous report 28 but is supported by the outcomes of a multitude of studies. 17,[29][30][31] Hence, negative correlations between CRP and relative bone variables, as found in this study, may represent an early indicator for the negative effect of chronic inflammation, which after prolonged exposure might result in decreased absolute bone mass and strength, as reported in other studies. 17,[29][30][31] In summary, we conclude that high body fat percentage was associated with lower relative bone mass and strength despite normal habitual muscle force in premenopausal women, indicating that high body fat percentage compromised the functional muscle-bone unit in these individuals.…”
Section: Discussionsupporting
confidence: 57%
“…Our result that CRP plasma concentration was negatively correlated with relative bone mass and strength values is in contrast to a previous report 28 but is supported by the outcomes of a multitude of studies. 17,[29][30][31] Hence, negative correlations between CRP and relative bone variables, as found in this study, may represent an early indicator for the negative effect of chronic inflammation, which after prolonged exposure might result in decreased absolute bone mass and strength, as reported in other studies. 17,[29][30][31] In summary, we conclude that high body fat percentage was associated with lower relative bone mass and strength despite normal habitual muscle force in premenopausal women, indicating that high body fat percentage compromised the functional muscle-bone unit in these individuals.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, Sponholtz et al, found that CRP was positively and significantly associated with femoral neck BMD in women shortly after menopause among hormone therapy users (mean age 59y) [30]. In terms of fracture risk, several studies have also reported no association between elevated CRP and low BMD, despite a higher fracture risk [21,22,24,31].…”
Section: Discussionmentioning
confidence: 99%
“…(28)(29)(30) Mechanisms that have been proposed to explain the effects of visceral adiposity on end-organ disease include the portal free fatty acid theory in which VAT might alter lipoprotein metabolism by inducing an overproduction of large triglyceriderich very low density lipoproteins, (31) and secretion of proinflammatory adipocyte-derived cytokines (10) that may have deleterious effects on the skeleton. (32,33) There are several strengths of our study. First we are the first study using state-of-the-art imaging to measure VAT and stateof-the-art measures of bone microarchitecture in the cortical and trabecular compartments.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%